A long-term atmospheric baseline for intercontinental exchange of airborne pathogens. (January 2022) - Triadó-Margarit, Xavier; Cáliz, Joan; Casamayor, Emilio O.
Graphical abstract: Highlights: Phytopathogens were the infectious agent predominant above the boundary layer. Consistent interannual dynamics were uncovered with taxa foreseeable over time. Fungi showed abundances and recurrences with high specificity and fidelity. Abstract: The atmosphere is a potential pathway for global-scale and long-range dispersal of viable microorganisms, promoting biological interconnections among the total environment. We aimed to provide relevant baseline information for long-range long-term intercontinental exchange of potentially infectious airborne microorganisms of major interest in environmental and health-related disciplines. We used an interannual survey (7-y) with wet depositions fortnightly collected above the boundary layer (free troposphere) at a remote high-elevation LTER (Long-Term-Ecological-Research) site, analyzed by 16S and 18S rRNA genes, and compared to a database of 475 well-known pathogens. We applied a conservative approach on close relatives of pathogenic species (>98% identity) standing their theoretical upper limit for atmospheric baseline relative abundances. We identified c. 2–3% of the total airborne microbiota as potential pathogens. Their most frequent environmental origins were soil, aquatic, and anthropogenic sources. Phytopathogens (mostly fungi) were the potential infectious agents most widely present. We uncovered consistent interannual dynamics with taxa foreseeable over time (i.e., predictable seasonal behavior) and under recurrent environmental scenarios (e.g., Saharan dust intrusions), respectively, being highly valuable microbial forensic environmental indicators. Up to 8 bacterial and 21 fungal genera consistently showed temporal abundances and recurrences unevenly distributed. Incidence of allergenic fungi was lower in summer, and significantly higher in spring. Close relatives to Coccidioides posadasii consistently showed higher signals (i.e., high specificity and high fidelity) in winter, whereas Cryptococcus neoformans had a significant signal in spring. Along Saharan dust intrusions, the bacterial phytopathogens Acidovorax avenae and Agrobacterium tumefaciens and the fungal phytopathogens Pseudozyma hubeiensis and Peniophora sp. consistently showed higher signals. Potential human pathogens showed low proportion, being mostly fungal allergens. Microorganisms related to obligated human, amphibian and fish pathogens were commonly found in winter. More studies in remote field sites above the boundary layer will unveil whether or not a similar trend is found globally.